Design and implementation of a simple and efficient medium access control for high-speed wireless local area networks. - Priscoli, F.D.
This paper deals with the medium access control (MAC) subsystem which has been implemented in the MEDIAN project (wireless broadband LANs for professional and residential multimedia applications) belonging to the European Union's (EU's) advanced communications technologies and services (ACTS) program. The proposed MAC aims at providing a low complexity and efficient transport for asynchronous transfer mode (ATM) cells from a base station (BS), interfaced with an ATM local exchange (LEX), to ATM portable stations (PSs) and vice versa. A time division duplex (TDD) scheme is adopted in which uplink and downlink frame durations can be varied frame-by-frame, in order to fit the present uplink/downlink traffic mix. Moreover, in the uplink, a contention-free based technique is considered in which the slots are assigned to the calls depending on the present load of the PS uplink buffers
Keywords: 150 Mbit/s.; 60 GHz; ACTS program; ATM cells; ATM local exchange; ATM portable stations; EHF; European Union; MEDIAN project; TDD; Advanced communications technologies and services; Asynchronous transfer mode; Base station; Contention-free based technique; Downlink frame duration; High-speed wireless local area networks; Medium access control; Professional multimedia application; Residential multimedia application; Time division duplex; Uplink buffers; Uplink frame duration; Uplink/downlink traffic; Wireless broadband LAN